Investigating the South-South dimension of modernity and Islam: Circulating visions and ideas, intellectual figures, locations - Buchholt, Helmut; Stauth, Georg; Larif-Béatrix, Asma; Nelson, Cynthia; Klein-Hessling, Ruth; Khondker, Habib (Yearbook of the Sociology of Islam, 2000)
Abaza, Mona: Speculation on South-South connections, modernity and Islam. Larif-Beatrix, Asma: Behind the veil. Islam in Malaysia and Tunisia. Stauth, Georg: Histories of islamisation and local Islams between the Middle East and Southeast Asia. Theories and personalities. Loimeier, Roman: From the Cape to Istanbul. Transnational networks and communal conflicts. Nelson, Cynthia: Satyagraha. Ghandi's influence on an Egyptian feminist. Alatas, Syed Farid: Alatas and Shari'ati on socialism. Autonomous social science and occidentalism. Abaza, Mona: Sketches of three portraits of Hadhrami origin Southeast Asians. Khondker, Habib: The secular author and the religious readers. Rushdie, Nasrin and the Muslims in Bangladesh. Klein-Hessling, Ruth: Female agency in a local arena. A case study from Northern Sudan